8x-4-2x=6x-4

Simple and best practice solution for 8x-4-2x=6x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-4-2x=6x-4 equation:


Simplifying
8x + -4 + -2x = 6x + -4

Reorder the terms:
-4 + 8x + -2x = 6x + -4

Combine like terms: 8x + -2x = 6x
-4 + 6x = 6x + -4

Reorder the terms:
-4 + 6x = -4 + 6x

Add '4' to each side of the equation.
-4 + 4 + 6x = -4 + 4 + 6x

Combine like terms: -4 + 4 = 0
0 + 6x = -4 + 4 + 6x
6x = -4 + 4 + 6x

Combine like terms: -4 + 4 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -5(3-4a)=20 | | 1y=4x+283 | | 91375193459137451057+73452863568283456345384-661649589246861356218565= | | 6+2x=4x+8 | | 18x^2+8x-1=0 | | 26.6=1+0.25 | | 21=-5(7x+8) | | 2(2x+3)=21-3(x-2) | | 6(4w+8)=28 | | 4(4w+3)=5 | | -5(2t+6)=30 | | -10(s+2)=-14 | | 3x/4-1/3=1-2/3(x-1/6) | | -1(c-9)=12 | | 0.60000001+-3= | | 3x+4x*8x=9 | | .40(x+300)=.10(300)+.50x | | -10(s+2)=55 | | -6-4(1-2b)=22 | | -1(n-6)=3 | | 8-4-(3x+4)=1x+2 | | 29=-7k+8k | | 141+-51= | | 2x^5-24x^4+100x^3+400x^2+3750x+5000=0 | | 142000/74000 | | 74000/142000 | | 3x+2y=179 | | -0.2=y/3 | | 2/3(2x-3)=1/1/2(3x-2) | | 2/3-6/7=x | | 8b+3b=(8+3)b | | 12x-y=6 |

Equations solver categories